Coffin-Siris Syndrome in Two Sisters in Nepal - Ojha, Anil; Fong, Chin-To; Pandey, Arti Sharma (Journal of Nepal Paediatric Society, 2013)
Coffin-Siris syndrome (CSS) has the characteristic feature of brachydactyly of the fifth digit of hands and feet accompanying cognitive and developmental delay. There is an overlap of symptoms with other conditions making the diagnosis of CSS difficult. An algorithm to look for a set of characters was followed for diagnosis of CSS in two sisters in Nepal. This is the first case of CSS reported from this country. DOI: http://dx.doi.org/10.3126/jnps.v33i2.8079 J Nepal Paediatr Soc. 2013; 33(2):132-135